Systematic review of attachment and substance misuse: measurement and outcomes for clinical samples; and a grounded theory study: how non-treatment seeking substance users make sense of their behaviour - Lawson, Sarah (The University of Edinburgh, 2020)
Background/aims Attachment theory has become widely used to understand interpersonal difficulties and psychological distress in clinical practice. Individuals who have difficulties with substance misuse are thought to be more likely to have an insecure attachment style. Thus, display difficulties with emotion regulation and relating to themselves and others in a helpful way. This in turn is likely to impact on their expression of distress and their ability to engage with services. Policy and research has aimed to identify links with substance use and attachment and identify barriers to treatment retention and engagement. However, methodological difficulties related to measurement of attachment or only focusing on the views of individuals who have already accessed treatment, make it difficult to generalise the results. Therefore, this thesis aimed to systematically review literature exploring attachment, substance misuse and levels of psychological distress. Focusing on what assessment measures were used, what attachment profiles are linked to this population and any associations with psychological distress. In addition, it aimed to construct a grounded theory model of how non-treatment seeking individuals who use substances, make sense of their behaviour. Methods Two studies were conducted to address the research aims. Journal article 1 is a systematic review of the literature on attachment, substance misuse and psychological distress in clinical populations. Electronic databases were searched and any relevant published literature was identified and assessed for quality before the results were synthesised and combined narratively. Journal article 2 is a qualitative grounded theory study in the form of eight in depth interviews with non-treatment seeking individuals who use substances. Data was collected and analysed simultaneously to identify theoretical categories which were explored and expanded upon during subsequent interviews. Results Twenty-three studies were identified during the systematic review. Results indicate a general link between substance misuse, an insecure attachment style and increased psychological distress. However, heterogeneity in relation to measurement and samples and an overrepresentation of selfreport measures limit the generalisability of the results. The findings from the second study suggest that identity and relational variables influence treatment decisions for individuals who use substances. Conclusions The study provides further evidence for the link between attachment insecurity and substance misuse. Reported levels of psychological distress varied between different patterns of insecure attachment which may reflect under reporting of symptoms. This has important research and practice implications on being able to meet the needs of these individuals appropriately. The results also highlight the need to consider identity and relational factors in service design to improve treatment engagement and retention.
Keywords: attachment; substance misuse; systematic review; identity